Urgensi Redesain Kebijakan dan Sistem Penyelenggaraan Studi Keislaman pada Peskam STAIN Samarinda - M. Said Husin; Etty Nurbayani (FENOMENA, 2014)
This study explores the urgent of STAIN Samarinda Boarding College Program (PESKAM) to redesign both its policy and its instructional framework for the irregular Islamic studies system, academic year 2014/2015, viewed from various aspects. The first aspect is about the effectiveness of irregular Islamic studies instructional achievement run in (academic year) 2103/2014. The second aspect is the leaders of STAIN Samarinda political interests concerning with PESKAM empowerment including institutional, instructional design, financial suffort, and the staffs. The third aspect is the regular Islamic studies lecturers’ academic sensitivity. And the last aspect is concerning with the design reliability of irregular Islamic studies program. The research shows that redesign is a must. It is imperative for STAIN Samarinda to redesign both PESKAM policy and its instructional framework for the irregular Islamic studies system. First, the system run during academic year 2013/2014 could not be considered effective. It did not use any general academic standards and could not be approached in terms of modern instructional management and design, such as the evaluation system designed to know periodically both the competence that a learner (a student in PESKAM) must be about to master and the process run to do such instruction as well.  However, all staffs and those who were in charge of managing the program worked hard and did all their best. Second, irregular Islamic studies instruction is viewed as the spirit for PESKAM in general. Its valuable benefit meets the stakeholders’ need. Finally, it is the cornerstone which can be accredited as the prime aspect distinguishing STAIN Samarinda from any general university (PTN/PTS)